Pulse pressure and the risk of renal hyperfiltration in young adults: Results from Korea National Health and Nutrition Examination Survey (2010–2019) - Yang, Eunji; Park, Sang Ho; Lee, Seoyoung; Oh, Donghwan; Choi, Hoon Young; Park, Hyeong Cheon; Jhee, Jong Hyun (Frontiers in Medicine, 2022)
Background: High pulse pressure (PP) is associated with increased risk of decline of kidney function. However, little is known about the association between PP and RHF in young adults. This study aimed to evaluate the association between PP and RHF in healthy young adults. Methods: Data were retrieved from the Korea National Health and Nutrition Examination Survey from 2010 to 2019. A total of 10,365 participants aged 19-39 years with no hypertension and normal kidney function were analyzed. RHF was defined as logarithm transformed estimated glomerular filtration rate (eGFR) with residuals >90th percentile after adjustment for sex, logarithm transformed age, weight and height. Participants were divided into tertile based on PP levels. Results: The prevalence of RHF was higher in higher PP tertile group (6.6%, 10.5%, and 12.7% in T1, T2, and T3; P for trend<0.001). In multivariable logistic regression analyses, the risk for RHF was increased in higher PP tertiles compared to the lowest tertile [odds ratio (OR), 1.42; 95% confidence interval (CI), 1.19 - 1.69 in T2; OR, 1.44; 95% CI, 1.20 - 1.73 in T3]. When PP levels were treated as continuous variable, the risk of RHF was increased 2.36 per 1.0 increase of PP (P<0.001). In subgroup analyses stratified sex, histories of diabetes or dyslipidemia, and isolated systolic hypertension or isolated diastolic hypertension, there were no significant interactions with PP for the risk for RHF, suggesting that high PP was associated with increased risk of RHF regardless of subgroups. However, the subgroup with BMI showed significant interaction with PP for the risk of RHF, indicating that participants with BMI ≥25 kg/m2 were at higher risk of RHF with increasing PP levels than those with BMI <25 kg/m2 (OR, 1.89; 95% CI, 1.25-2.87 in BMI <25 kg/m2; OR, 3.16; 95% CI, 1.74-5.73 in BMI ≥25 kg/m2; P for interaction = 0.01). Conclusions: High PP is associated with an increased risk of RHF in healthy young adults and this association is prominent in obese young adults. The assessment of PP and associated RHF may give benefit to early detect the potential risk of CKD development in young adults.